Effect of regular exercise on the levels of subfatin and asprosin: a trial with different types of exercise - Akbulut, T.; Cinar, V; Ugur, K.; Yardim, M.; Karagoz, Z. K.; Aydin, S. (Verduci Publisher, 2022)
OBJECTIVE: Subfatin (Metrnl) and asprosin are associated with metabolic diseases. such as obesity and diabetes. Exercise is among the most important regulators of health in humans and has been previously demonstrated to regulate these parameters. The present study aimed to investigate the effects of different types of regular exercises on levels of subfatin, asprosin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), uric acid. and glucose. MATERIALS AND METHODS: The study included 120 young and healthy males. who participated in the study voluntarily. These participants were randomly divided into four groups, such as control (C). aerobic exercise (AE), intermittent (HIIT), and resistance exercise (RE) groups. Additionally, all the groups had equal numbers of participants. First. the subjects in the exercise group were made familiar with the exercise regime for two weeks. Then, they performed regular exercises. three days a week for eight weeks. Blood samples were collected from the participants at the beginning and end of the study. Subfatin and asprosin levels were analyzed using the ELISA method. AST, ALT, uric acid, and glucose levels were analyzed using the AutoAnalyzer. RESULTS: No differences were observed in pretest values between the groups (p>0.05). Assessment of intragroup changes demonstrated no significant changes in the control group. In the comparisons, statistically significant changes were recorded in the levels of subfatin. asprosin, and glucose in all exercise groups. Particularly. differences were observed in the levels of AST and uric acid in the AE and HIIT groups while differences in ALT levels were observed only in the AE group (p<0.05). CONCLUSIONS: In the conclusion of the study, different types of exercises caused significant changes in subfatin and asprosin levels. Thus, these results suggested that the parameters associated with metabolic diseases could be controlled with the aid of regular exercises.
Keywords: Exercise; Metabolic diseases; Meteorin-like; Bio-chemistry; Glucose